Answer:
I believe it’s b could be wrong if I am I’m very sorry
Step-by-step explanation:
By evaluating the quadratic function, we will see that the differential quotient is:
![\frac{f(2 + h) - f(2)}{h} = 8 + h](https://tex.z-dn.net/?f=%5Cfrac%7Bf%282%20%2B%20h%29%20-%20f%282%29%7D%7Bh%7D%20%3D%208%20%2B%20h)
<h3>
How to get (f(2 + h) - f(2))/h?</h3>
Here we have the quadratic function:
![f(x) = x^2 + 4x + 5](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%5E2%20%2B%204x%20%2B%205)
Evaluating the quadratic equation we get:
![\frac{f(2 + h) - f(2)}{h}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%282%20%2B%20h%29%20-%20f%282%29%7D%7Bh%7D)
So we need to replace the x-variable by "2 + h" and "2" respectively.
Replacing the function in the differential quotient:
![\frac{(2 + h)^2 + 4*(2 + h) + 5 - (2)^2 - 4*2 - 5}{h} \\\\\frac{4 + 2*2h + h^2 + 8 + 4h - 4 - 8 }{h} \\\\\frac{ 2*2h + h^2 + 4h }{h} = \frac{8h + h^2}{h}](https://tex.z-dn.net/?f=%5Cfrac%7B%282%20%2B%20h%29%5E2%20%2B%204%2A%282%20%2B%20h%29%20%2B%205%20-%20%282%29%5E2%20-%204%2A2%20-%205%7D%7Bh%7D%20%5C%5C%5C%5C%5Cfrac%7B4%20%2B%202%2A2h%20%2B%20h%5E2%20%2B%208%20%2B%204h%20%20-%204%20-%208%20%7D%7Bh%7D%20%5C%5C%5C%5C%5Cfrac%7B%202%2A2h%20%2B%20h%5E2%20%20%2B%204h%20%20%20%7D%7Bh%7D%20%3D%20%5Cfrac%7B8h%20%2B%20h%5E2%7D%7Bh%7D)
If we simplify that last fraction, we get:
![\frac{8h + h^2}{h} = 8 + h](https://tex.z-dn.net/?f=%5Cfrac%7B8h%20%2B%20h%5E2%7D%7Bh%7D%20%3D%208%20%2B%20h)
The third option is the correct one, the differential quotient is equal to 8 + 4.
If you want to learn more about quadratic functions:
brainly.com/question/1214333
#SPJ1
Answer:
1. 13+10i
2. 28-(-4i)
3. -14-1i
4. 4 -i
5. 15+ 10i
6.8 - 5i^2
Step-by-step explanation:
3,322.609847222222 mph. First covert miles to km. This distance is 239227.909 miles. then divide this by the number of hours which is number of days times 24. It took 3 days so it is 72 hours. After diving 239227.909/72 you get your answer of 3,322.609847222222 mph
Answer:
(b)0.56
(c)0.38
Step-by-step explanation:
(a)
P(Ben Pass) =0.8
Therefore: P(Ben fails)=1-0.8 =0.2
P(Tom Pass) =0.7
Therefore: P(Tom fails)=1-0.7 =0.3
See attached for the completed tree diagram
(b)Probability that both will pass
P(both will pass)=P(Ben pass and Tom pass)
=P(Ben pass) X P(Tom pass)
=0.8 X 0.7
=0.56
(c)The probability that only one of them will pass
Since either Tom or Ben can pass, we have:
P(only one of them will pass)
=P(Ben pass and Tom fails OR Ben Fails and Tom Pass)
=P(Ben pass and Tom fails)+P(Ben Fails and Tom Pass)
=(0.8 X 0.3) + (0.2 X 0.7)
=0.24 + 0.14
=0.38